SCIENTIFIC PROJECT COVERAGE IN VEGETABLE PLANT BREEDING (SESSION OF JOINT BOARD OF MINISTRY OF AGRICULTURE AND PRESIDIUM OF RUSSIAN ACADEMY OF AGRICULTURAL SCIENCE) - I.V. Savchenko; A.M. Medvedev; N.I. Bocharnikova (Овощи России, 2011)
On 18 August, 2011 the joint meeting of Ministry Board of Agriculture of Russian Federation and Presidium of Russian Academy of Agricultural Science was held.